Eye tracking function in the early detection of mild cognitive impairment (MCI) - Ashkboos akbari; mahgol tavakoli; Amirhasan Monajemi (پژوهش‌های علوم شناختی و رفتاری, 2021)
Early detection of dementia in the elderly has always been challenging. This study aimed to evaluate the eye tracking of the elderly to assess the ability of this tool in the early detection of mild cognitive impairment as the prodromal stage for dementia. For this purpose, 60 elderly people of Farhangian Retirees Association in Isfahan were selected by convenience sampling and NUCOG test was performed on them for screening. Then, three groups of 8 people (healthy, with dementia and mild cognitive impairment) were randomly selected and evaluated in eye-tracking tasks. The results showed that the healthy elderly had the highest and the elderly with dementia the least attention and recurrence of repetitive images in a two-minute pause. Individuals with mild cognitive impairment were significantly between these two spectrums (P<0/01). It seems that with the help of eye-tracking, a quick and inexpensive diagnosis for mild cognitive impairment can be achieved.